2016
DOI: 10.1007/s40090-016-0089-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hybridization on the value-added activated carbon materials

Abstract: This paper provides a concise review of recent advances in activated carbon (AC) and its corresponding modified material. Topics covered in this work include the synthesis and characterization of AC as the feedstock materials, as well as the properties and applications of the subsequent hybrid material for different industries. Numerous research studies have since reported remarkable physical, chemical, thermal, conductivity, porosity, and mechanical (stiffness and strength) properties of AC in different types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 141 publications
(115 reference statements)
0
4
0
Order By: Relevance
“…AC has relatively high affinity towards Pb(II), Cd(II), Cu(II), Ni(II), and Zn(II) [6][7][8][9]. Application of AC in powder form in the adsorption process has some disadvantages, such as agglomeration and filtration difficulties due to very fine particles that form a dense filter layer in slurry phase operations [10]. Additionally, a huge volume of adsorbent is required in the adsorption process.…”
Section: Introductionmentioning
confidence: 99%
“…AC has relatively high affinity towards Pb(II), Cd(II), Cu(II), Ni(II), and Zn(II) [6][7][8][9]. Application of AC in powder form in the adsorption process has some disadvantages, such as agglomeration and filtration difficulties due to very fine particles that form a dense filter layer in slurry phase operations [10]. Additionally, a huge volume of adsorbent is required in the adsorption process.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is reported that the AC/metal composite may exhibit high transfer characteristics and effective catalytic/adsorptive properties [21,22], it is believed that the difficulty of keeping the metal in the zero-valent state on AC surface may be a reason for the limited number of papers. Especially the oxygen-containing surface functional groups on the AC surface have great influence on the oxidation of transition metals [23].…”
Section: Introductionmentioning
confidence: 99%
“…SCW condition also allows the nanoparticles to deposit on a support surface and inside the pores in well-dispersed conditions [9]. Furthermore, carbonsupported metal oxides are of interest in an adsorption technique because porous activated carbon can be incorporated with metal oxides by various functional groups on the own surface, and it has a large specific surface area and pore distributions that are required for the removal of pollutants [10][11][12]. Due to these advantages, the use of activated carbon, often as a composite material with metal oxides, in wastewater treatment is increasing dramatically [13].…”
Section: Introductionmentioning
confidence: 99%